Moebius Sequence: case report and literature review - Rafael Marques Franco (Revista da Faculdade de Ciências Médicas de Sorocaba, 2011)
ABSTRACT We report the case of a elderly pregnant woman’s newborn presenting Moebius sequence, a rare disease characterized by paralysis of the sixth and seventh cranial nerves. A genetic defect was suspected at the nursery, where the presence of labial rima to the right was noticed. The newborn was sent to the clinical genetics ambulatory where the diagnosis was confirmed after clinical assessment.